Optimization of Silicon Nanocomposite Anodes for High-Energy-Density Lithium-Ion Batteries - Shao, Linqian (Simen Owen Academic Proceedings Series, 2026)
Lithium-ion batteries (LIBs) are vital for energy storage in applications like consumer electronics and electric vehicles. Silicon-based anodes offer high theoretical capacity, but challenges remain, including large volume expansion, low Coulombic efficiency, and short cycle life. Current strategies, such as nanostructuring and carbon hybridization, struggle to balance performance with scalability and durability. This study introduces a silicon-graphene-polyacrylic acid (Si/G/PAA) nanocomposite anode, integrating structural, interfacial, and processing innovations. The key advancement is the dual-phase confinement of Si nanoparticles using reduced graphene oxide (rGO) and crosslinked PAA, along with engineered mesoporosity to accommodate Si expansion and interfacial passivation via GO wrapping. The process is water-based and NMP-free, ensuring industrial scalability. The Si/G/PAA anode achieves an initial Coulombic efficiency of 83 ± 1% and 85 ± 2% capacity retention after 200 cycles at 3.5 mAh cm⁻² areal capacity. Full-cell tests with LiFePO4 cathodes at 45°C show over 80% capacity retention after 300 cycles. This work provides a scalable, high-performance anode solution, addressing key LIB challenges and demonstrating both academic and practical significance for future energy storage technologies.